[RETRACTED] Physical Elements of Accessibility for Wayfinding in an Information Deficit Tourism Area - Laksita, Isabella Nindya; Marcillia, Syam Rachma (Departemen Arsitektur Fakultas Teknik Universitas Brawijaya, Indonesia, 2021)
This article is a duplication of an article written by the same author under the same title in NATURE: National Academic Journal of Architecture Vol 7, No 2 (2020).The authors contacted the Editor shortly after publication stating that the same article has been published in another journal due to long journal processing in RUAS (Review of Urbanism and Architectural Studies).The Editorial Board wishes to apologize for publishing the following article in the RUAS Vol 19, No 1 June 2021 edition.